Treated Wastewater Irrigation—A Review - Mahmoud S. Hashem (Water, 2021)
As the most important resource for life, water has been a central issue on the international agenda for several decades. Yet, the world’s supply of clean freshwater is steadily decreasing due to extensive agricultural demand for irrigated lands. Therefore, water resources should be used with greater efficiency, and the use of non-traditional water resources, such as Treated Wastewater (TW), should be increased. Reusing TW could be an alternative option to increase water resources. Thus, many countries have decided to turn wastewater into an irrigation resource to help meet urban demand and address water shortages. However, because of the nature of that water, there are potential problems associated with its use in irrigation. Some of the major concerns are health hazards, salinity build-up, and toxicity hazards. The objectives of this comprehensive literature review are to illuminate the importance of using TW in irrigation as an alternative freshwater source and to assess the effects of its use on soil fertility and other soil properties, plants, and public health. The literature review reveals that TW reuse has become part of the extension program for boosting water resource utilization. However, the uncontrolled application of such waters has many unfavorable effects on both soils and plants, especially in the long-term. To reduce these unfavorable effects when using TW in irrigation, proper guidelines for wastewater reuse and management should be followed to limit negative effects significantly.